“Estudio de los embarazos de riesgo y su repercusión en morbimortalidad perinatal en el hospital apoyo Iquitos “Cesar Garayar García” periodo noviembre 1996 – julio 1997” - Vargas Riva, Lloy (1998)
The developing countries such as ours, have a higher incidence of perinatal morbidity and mortality, for which our study provided the determination of pregnancy risk in perinatal mortality and morbidity, the incidence of risk pregnancies, the most frequent causes of perinatal morbidity and mortality and relative risk influencing perinatal morbidity and mortality. A study of applied type of cohort with prospective collection in support of Hospital! quitos "César Garayar García" during the months of November 1996 - July 1997, obtaining the following results of the total of 1,855 births that occurred in the Hospital support! quitos "César Garayar García" during the period November 1996 - July 1997, taking a study population of 412 pregnant women, of which 309 cases were pregnant women at high risk and 103 pregnant women of low risk , of which, the incidence of those pregnancies of high risk was 166.58 x 1000-pregnancies, having as causes more frequently...